The Effect Of Supervision And Work Discipline On Employee Performance Moderated By Motivation At PT Bank North Sharia Padangsidimpuan Branch - Hilman Saleh Daulay; Abdi Sugiarto (Yayasan Multidimensi Kreatif, 2025)
The purpose of this research is to determine and analyze the influence of supervision and work discipline on employee performance which is moderated by work motivation at PT. Bank Sumut Syariah Padangsidempuan Branch. This research was carried out at PT. Bank Sumut Syariah Padangsidempuan Branch. The type of research is associative quantitative. The sample in this study was 22 employees with ASN and honorary status at PT. Bank Sumut Syariah Padangsidempuan Branch. The sampling technique in this study used the entire population of 22 people. The research results show that supervision has a significant influence on employee motivation as shown by the T-Statistic value of 3,784 > 1.96 and the P Value of 0.001 < 0.05. Work discipline has a significant effect on employee performance with a T-Statistic value of 6.197 > 1.96 with a P-Value of 0.000 < 0.05. Work Discipline has a significant effect on Employee Work Motivation, this can be seen from the results of the T-Statistic value of 2.828 > 1.96 with a P-Value value of 0.010 < 0.05. In the indirect effect, the results show that work motivation does not have a role as a moderating variable in explaining the relationship between supervision and work discipline and employee performance. This shows that improvements in supervision and work discipline cannot increase work motivation, which ultimately contributes to improving employee performance at PT. Bank Sumut Syariah Padangsidempuan Branch.